The Politeness Strategies Used By Ketut Permata Juliastrid As Winner Miss Cosmo 2024 - Ade Irawan; Agus Salim Mansyur; Fourus Huzanatul Abqoriyyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the politeness strategies used by the winner of Miss Cosmo 2024, Ketut Permata Juliastrid, in a talk show on the IDN Times YouTube channel. The main objective of this research is to find out the type and purpose of the politeness strategies used. Brown and Levinson's politeness theory is used in this study to determine the types of politeness strategies used and also the purpose of the politeness strategy used. This study used a descriptive qualitative approach as its methodology. Information was collected from transcripts of talk show conversations, which were then categorized according to the types of politeness strategies used. The results of the analysis based on the data analysis, 8 politeness strategies were identified. It consists of 4 positive politeness strategies, 2 negative politeness strategies, and 2 bald on record strategies.. The findings of this study confirm that positive politeness strategies mostly found in communication in a talk show.